University professors in the final phase of their careers: a case study in Chile - Almonacid-Fierro, Alejandro; Valdebenito, Karla; Urrutia, Jessica Mondaca; Morales, Karen (Intelektual Pustaka Media Utama, 2025)
The article endeavors to analyze the career path of university professors in the latter stage of their profession and seeks to comprehend the methods of configuring and reconfiguring knowledge related to university instruction. It specifically focuses on professors who hold over 30 years of teaching experience in academia. The study utilized the interpretative paradigm and qualitative methodology, employing semi-structured interviews as the data collection technique. The sample comprised ten teachers and the interviews were conducted between September and November 2022. The findings revealed that university teaching relies on three fundamental aspects: pedagogical construction, affective-emotional aspects of teaching, and barriers to teaching in higher education. The study results offer diverse perspectives on the challenges and opportunities that shape the higher education instructional environment, particularly regarding teaching approaches and methodologies. The research provides novel insights into the multifaceted components that define university pedagogy and the process of professors transitioning into retirement. It establishes a significant foundation for developing more efficacious and adaptable educational policies and practices in the dynamic realm of higher education.